Answer:
Step-by-step explanation:In an inverse variation, the relationship between x and y can be represented by the equation y = k/x, where k is a constant of variation.
Given that y = 2 when x = 3, we can substitute these values into the equation to find the value of k:
2 = k/3
To solve for k, we can multiply both sides of the equation by 3:
2 * 3 = k
6 = k
Now that we have found the value of k, we can write the inverse variation equation as:
y = 6/x
Therefore, the inverse variation equation that shows the relationship between x and y is y = 6/x.